2014
DOI: 10.1111/bph.12753
|View full text |Cite
|
Sign up to set email alerts
|

Single housing during early adolescence causes time‐, area‐ and peptide‐specific alterations in endogenous opioids of rat brain

Abstract: Background and PurposeA number of experimental procedures require single housing to assess individual behaviour and physiological responses to pharmacological treatments. The endogenous opioids are closely linked to social interaction, especially early in life, and disturbance in the social environment may affect opioid peptides and thereby confound experimental outcome. The aim of the present study was to examine time-dependent effects of single housing on opioid peptides in rats.Experimental ApproachEarly ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Short-term single housing, that is, 24 hours, mainly affected regions involved in the stress response, that is, pitui-tary, hypothalamus, amygdala, hippocampus, and cortex regions (Watts, 2000), which suggests that this is an acute stressor in both ages. A large impact of single housing on MEAP levels is in agreement with recent findings (Granholm et al, 2014). An increase in MEAP levels as seen here in the early stages of single housing could be an indicator of an activated stress-adapting system.…”
Section: Short-term Single Housing Alcohol Intake and Age-specific supporting
confidence: 93%
See 2 more Smart Citations
“…Short-term single housing, that is, 24 hours, mainly affected regions involved in the stress response, that is, pitui-tary, hypothalamus, amygdala, hippocampus, and cortex regions (Watts, 2000), which suggests that this is an acute stressor in both ages. A large impact of single housing on MEAP levels is in agreement with recent findings (Granholm et al, 2014). An increase in MEAP levels as seen here in the early stages of single housing could be an indicator of an activated stress-adapting system.…”
Section: Short-term Single Housing Alcohol Intake and Age-specific supporting
confidence: 93%
“…A large impact of single housing on MEAP levels is in agreement with recent findings (Granholm et al., 2014). An increase in MEAP levels as seen here in the early stages of single housing could be an indicator of an activated stress-adapting system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences for adult vs. adolescent rats must be compared carefully as they could be due to age, ethanol administration model, or both. In both adult and adolescent rats, the central levels of endogenous opioids interact with housing conditions (i.e., single or group housed) and ethanol intake ( 19 , 20 ). These aforementioned studies show the profound importance of the experimental settings when working with ethanol models in rats.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid biological littermates, the litters were cross-fostered and mixed on the day of birth (postnatal day, PND, 0) so each litter contained four females and six males. Previous studies have shown that single housing affects brain levels of endogenous opioid peptides in adolescent rats ( 19 , 20 ), so on PND 21 the pups were weaned and group housed (2–3 rats per cage) to avoid confounding factors.…”
Section: Methodsmentioning
confidence: 99%